Improving user experience of color palette extraction by using interactive visualization based on hierarchical color model - Karim, Raja Mubashar; Jeong, Taehong; Ha, Hyoji; Ho, Jaejong; Lee, Kyungwon; Shin, Hyun Joon (International Journal of Human Computer Studies, 2023)
Extracting color palettes from an image is a common practice used by artists in different visual domains. In this study, we introduce a novel tool for extracting color palettes from an image. Based on the hierarchical color model (HCM) (Jeong et al. (2019)), we develop a prototype user interface system comprising novel interactions and visualization. Our visualization is a node-link diagram tailored for the HCM; the accompanying interactions originate from the hierarchical structure. We evaluate our prototype system by performing a usability test and comparing it with contemporary alternatives for professional usage. The results from the user study validate the effectiveness of the presented approach. We also find a few user requirements that can be useful in the further development of the related tools. Moreover, we expect that the proposed interactive visualization can facilitate additional studies on the HCM. The prototype is available in the following URL: https://int-vis-hcm.web.app.
Keywords: Authoring color palette; Color models; Colour palette; Hierarchical representation; Hierarchical structures; Interactive visualizations; Interface system; Node-link diagrams; Prototype system; Users' experiences; Authoring color palette; Hierarchical representation; Interactive visualization